Pelatihan Penyusunan Narasi dan Peta Sebaran Potensi Wisata Bagi Pokdarwis Golo Cucu - Roseven Rudiyanto; Margareta Julyanti (Jurnal Abdimas Pariwisata, 2022)
Training for Preparation of Narratives and Distribution Map of Tourism Potential for Pokdarwis Golo Cucu Kempo Village is one of the villages in West Manggarai Regency which has been designated as a tourist village. The community group that is involved in developing tourism potential in this village is Pokdarwis Golo Cucu. The problem faced by Pokdarwis is that there is still no information about the tourism potential in Kempo Village, such as narratives and maps of the distribution of tourism potential. Therefore, the purpose of this activity is for Pokdarwis members to be able to compose narratives and potential distribution maps as information to be shared with visitors. This activity uses the focus group discussion method. The result of this activity is that there are 15 natural and cultural tourism potentials that can become tourist attractions in Kempo Village along with narratives and maps of the distribution of tourism potential. As a suggestion, the structured narrative can be refined again to present interesting information. In addition, narratives can be posted on information boards and social media as promotional materials. The tourism potential distribution map can also be refined by using GIS applications and determining points using GPS, so that the resulting map is more precise..